Vlijanie interval'noj trenirovki na gipertrofiju myšc: poperecnoe issledovani - Miroshnikov, A. B.; Volkov, V. V.; Smolenskiy, A. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The purpose of the study: to evaluate how high-intensity work affects oxidizing abilities, strength and hypertrophy of working muscles in power sports athletes. The study involved 35 representatives of power sports (powerlifting), body weight - 105.3 ± 5.3 kg, the average age of male athletes was 30 ± 5.4 years. Before and after the study, all athletes under-went a comprehensive examination, including: questioning, examination, ergospirometry, ultrasonographic measurements of the anatomical cross-sectional area of the quadriceps femoris, measurement of the level of oxygenation of the lateral head of the quadriceps femoris, and assessment of the maximum voluntary strength of the quadriceps femoris. According to the results of the study, it is possible to note not only a 72% decrease in oxygenation, but also an increase in work capacity at the level of maximum oxygen consumption and working time for power sports athletes. Also, regular high-intensity training on a bicycle ergometer causes muscle hypertrophy, which leads to an increase in the strength of the quadriceps femoris muscle by 6.5%. The aerobic workout training protocol that we developed, taking into account metabolic variables, will allow athletes to efficiently and safely increase the oxidizing abilities of working muscles, without losing their main strength indicators.